Muscle Injury in Sports Activity - Etiology, Classification and Treatment - B.A. Antohe; M. Rata; B.C. Rata; G. Rata (Editura Universitatii Transilvania din Brasov, 2022)
Muscle lesions are among the most common injuries encountered in performance sports. Despite their high incidence, their diagnosis, classification, and treatment are constantly being debated. Most of the time, the severity of the injury indicates the recovery strategy (conservative, physical therapy, surgical, etc). Currently, due to advances in medical, pharmacological, and physical therapy, the treatment of muscle injuries can be greatly improved. Incomplete or incorrect recovery from a muscle injury can have a series of negative effects (financial or sports performance), which can affect the long-term career of athletes. Considering the incidence and costs that an injury can generate, in this paper, we set out to identify and present the latest approaches, used by specialists in the field, to facilitate the fastest recovery of athletes.